DIFFERENCE OF DIVORCE DETERMINATION IN INDONESIA: A STUDY SYSTEMATIC LITERATURE REVIEW - Luluk Latifah; Iskandar Ritonga (Universitas Airlangga, 2022)
The divorce rate is getting more and more concerning. The number of divorce rate shows a significant increase both nationally and regionally in Indonesia. During 2019, there were 480,618 divorce cases. This divorce rate increased by 18% compared to the previous year which amounted to 408,202 cases. This paper aims to determine the determinants of divorce in Indonesia, using a Systematic Literature Review of 20 journals published by indexed publishers. The results based on the mapping state that the differentiation of the determinants of divorce in Indonesia very much depends on each region. However, all of them can be mapped into 16 factors that cause divorce, namely: economic factors, responsibility, continuous quarrels, harmony, infidelity, domestic violence, jealousy, leaving a partner, forced marriage, apostasy/leaving Islam, drunkenness and gambling, obstructed communication, interference/third party intervention, incompatibility, unhealthy polygamy, and moral crisis. The conclusion of this study is that the strongest determinant of divorce in Indonesia in each region is the economic factor. Economic factors are the strongest factor causing divorce, because the cause of divorce in almost all areas with the highest frequency and the highest percentage is also compared to other causes of divorce.